2014
DOI: 10.2215/cjn.03790414
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Creatinine Excretion, Bioelectrical Impedance Analysis, and Clinical Outcomes in Patients with CKD

Abstract: Background and objectives Previous studies in chronic disease states have demonstrated an association between lower urinary creatinine excretion (UCr) and increased mortality, a finding presumed to reflect the effect of low muscle mass on clinical outcomes. Little is known about the relationship between UCr and other measures of body composition in terms of the ability to predict outcomes of interest.Design, setting, participants, & measurements Using data from the Chronic Renal Insufficiency Cohort (CRIC), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 45 publications
(34 reference statements)
3
61
2
Order By: Relevance
“…The rationale for indexing biomarkers to urine creatinine is to account for differences in urine concentration (20). Some studies have suggested that lower urinary creatinine concentration itself may be associated with CKD progression, perhaps because low urine creatinine concentration reflects impaired urine concentrating ability and thus, a dimension of CKD beyond eGFR, such as lower lean body mass (20)(21)(22). Importantly, we did not find an association of 1/urinary Cr with ESRD, suggesting that the indexed results do not simply reflect the association of 1/urinary Cr with the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for indexing biomarkers to urine creatinine is to account for differences in urine concentration (20). Some studies have suggested that lower urinary creatinine concentration itself may be associated with CKD progression, perhaps because low urine creatinine concentration reflects impaired urine concentrating ability and thus, a dimension of CKD beyond eGFR, such as lower lean body mass (20)(21)(22). Importantly, we did not find an association of 1/urinary Cr with ESRD, suggesting that the indexed results do not simply reflect the association of 1/urinary Cr with the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…First, we adjusted age, sex, race, urinary creatinine excretion, and CRIC clinic site in the multivariable models. 36 Second, we added important risk factors for CKD progression in the multivariable models. Furthermore, eGFR at baseline was included in the multivariable models.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Available estimating equations do not have verified accuracy in various non-United States and European white and black racial/ethnic groups (30) or those at extremes of muscle mass or body size or who consume vegetarian or vegan diets. We still have much to learn about relationships between BMI, muscle mass, and creatinine excretion (21,65,66). Furthermore, the serum creatinine concentration on which these formulas are based may be influenced by diet, creatine supplements, and certain medications (i.e., trimethoprim and cimetidine).…”
Section: Discussionmentioning
confidence: 99%